Large-size ultrathin ceramic-based solid electrolyte diaphragm and preparation method thereof

By applying pretension during the sintering process of ceramic-based solid electrolyte separators, the problems of low mechanical strength and ionic conductivity of large-sized and ultra-thin ceramic-based solid electrolyte separators in the prior art are solved, and separators with high density and excellent electrochemical performance are achieved, meeting the needs of all-solid lithium batteries.

CN119651044APending Publication Date: 2025-03-18NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411686094.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ceramic-based solid electrolyte separators have low mechanical strength, low room temperature ion conductivity, low density and poor flatness in large sizes and ultra-thin conditions, making it difficult to meet the needs of all-solid lithium batteries.

Method used

Using specific chemical composition and innovative preparation processes, large-sized blanks are prepared by casting method, and pretension is applied during the sintering process to achieve uniform flatness and high density structure of ceramic-based solid electrolyte membranes.

Benefits of technology

The mechanical strength and ionic conductivity of large-size ceramic-based solid electrolyte separators are significantly improved, ensuring the high density and excellent electrochemical performance of the separators, and meeting the demand for high-performance separators for all-solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651044A_ABST
    Figure CN119651044A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a large-size ultrathin ceramic-based solid electrolyte diaphragm, which comprises the following steps: S1, carrying out ball-milling dispersion on solid electrolyte powder, a dispersant, a binder, a plasticizer and a solvent to form homogenized tape-casting slurry; s2, carrying out curtain coating and drying to obtain a single-layer electrolyte biscuit; s3, laminating and hot-pressing are carried out, and a green body with a certain thickness is obtained; s4, primary cutting is conducted according to the needed shape and size; s5, performing one-step high-temperature heat treatment or two-step high-temperature heat treatment in a manner of applying pretension to obtain a ceramic-based solid electrolyte diaphragm sheet; and S6, performing secondary cutting to obtain a finished product of the large-size ultrathin ceramic-based solid electrolyte diaphragm. According to the preparation method disclosed by the invention, the mechanical strength and the ionic conductivity of the ceramic-based solid electrolyte diaphragm are improved, the characteristics of large size and ultra-thinness of the ceramic-based solid electrolyte diaphragm are realized, and the requirement of an all-solid-state lithium battery on a high-performance diaphragm is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic-based solid electrolyte diaphragms, and in particular to a large-sized ultra-thin ceramic-based solid electrolyte diaphragm and a preparation method thereof. Background Art

[0002] As people raise the standard of energy density of lithium-ion batteries and the existence of safety issues of liquid electrolytes themselves, such as volatility, flammability and poor chemical stability, traditional liquid lithium-ion batteries are difficult to be more widely used. Solid electrolytes have the advantages of high ion conductivity, good safety and long cycle life, and are an ideal substitute for organic liquid electrolytes. Solid electrolytes are the core part of all-solid-state lithium-ion batteries. Their function is to ensure the transfer of lithium ions between the positive and negative active materials, and at the same time, they act as a diaphragm to separate the positive and negative electrodes to prevent internal short circuits.

[0003] Existing inorganic solid electrolyte materials have high room temperature ionic conductivity, which has attracted the attention of researchers at home and abroad. In order to improve the energy density of all-solid-state lithium-ion batteries, the thickness of solid electrolyte membranes tends to be ultra-thin, but the performance of the membrane will drop drastically. The ultra-thin oxide ceramic membranes currently prepared using this material have the disadvantages of low mechanical strength, low room temperature ionic conductivity, poor processing performance, and poor flatness, especially the preparation of ceramic-based solid electrolyte membranes with medium and large sizes of 10cm×10cm and above and thickness of less than 100μm is more difficult. At the same time, it is also necessary to ensure that the ultra-thin solid ceramic-based solid electrolyte membrane has good mechanical strength, density and high room temperature ionic conductivity to meet the requirements of battery applications.

[0004] Ceramic-based solid electrolyte membranes are the key research direction of solid-state lithium batteries. The currently recognized production processes of ceramic-based solid electrolyte membranes mainly include wet and dry preparation. The wet preparation is to disperse the solid electrolyte in a solvent, add a certain amount of binder to form a uniformly dispersed slurry, use a scraper to coat the slurry on the base film, dry it to form a film, and then stack, hot press, debind, and sinter it to form a film. This process is simple to operate, the thickness of the solid electrolyte blank (including binder, etc.) is uniform and adjustable (the thickness can be as low as 30μm or less), and it can be prepared on a large area, which is conducive to improving the energy density of solid-state batteries. However, due to the limitations of debinding defects and sintering methods, the room temperature ionic conductivity of ultra-thin ceramic-based solid electrolyte membranes is lower than that of traditional cold-pressed sintering, the strength is reduced, and the flatness is poor, so mass production is very challenging. The dry preparation method is to mix solid electrolyte powder with a binder, and then produce a dry ceramic-based solid electrolyte membrane through processes such as dispersion, fiberization, and calendering film formation. The preparation cost is low, but the mechanical strength is low, the thickness is thick, and the processing performance is poor, which affects the energy density of the solid-state battery.

[0005] In general, the preparation methods of solid ceramic-based solid electrolyte membranes in the prior art have the disadvantages of low room temperature ionic conductivity, low mechanical strength, low density, poor flatness, and poor processing performance. In particular, when the size of the ceramic-based solid electrolyte membrane is larger and the thickness is thinner, the above-mentioned properties drop sharply, which cannot meet the current demand for ultra-thin and large-sized ceramic-based solid electrolyte membranes in all-solid-state lithium batteries, limiting mass production and application. Therefore, it is necessary to develop a large-size ultra-thin ceramic-based solid electrolyte membrane preparation method with high strength, high room temperature ionic conductivity, high density, controllable shape, and large-scale mass production. Summary of the invention

[0006] In view of the above shortcomings of the prior art, the present invention provides a large-sized ultra-thin ceramic-based solid electrolyte diaphragm to solve the technical problems of traditional diaphragms in mechanical strength, ionic conductivity, density, and large-sized ultra-thin preparation. The present invention achieves the mechanical strength and ionic conductivity of the large-sized ceramic-based solid-state ceramic-based solid electrolyte diaphragm significantly improved while maintaining the ultra-thin characteristics by adopting a specific chemical composition and an innovative preparation process, ensuring the high density and excellent electrochemical properties of the diaphragm, so that the diaphragm can meet the demand for high-performance diaphragms for all-solid-state lithium batteries.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0008] A method for preparing a large-sized ultra-thin ceramic-based solid electrolyte diaphragm, the preparation method comprising the following steps:

[0009] S1 slurry preparation: take a certain mass of solid electrolyte powder, add a certain proportion of dispersant, binder, plasticizer and solvent, and form a uniform casting slurry after ball milling and dispersion;

[0010] S2 tape casting and drying: the tape casting slurry obtained in step S1 is tape cast and dried to obtain a single-layer electrolyte blank;

[0011] S3 lamination hot pressing: lamination hot pressing the single-layer electrolyte green body obtained in step S2 according to the required thickness to obtain a green body of a certain thickness;

[0012] S4: cutting the green body obtained in step S3 into the required shape and size;

[0013] S5 heat treatment: the green body of a certain shape and size obtained in step S4 is subjected to a one-step high-temperature heat treatment or a two-step high-temperature heat treatment by applying pre-tension to obtain a ceramic-based solid electrolyte diaphragm sheet;

[0014] S6 secondary cutting: according to the required shape and size, a laser cutting machine is used to perform secondary cutting on the effective sintering area of ​​the ceramic-based solid electrolyte diaphragm sheet obtained in step S5, and finally a finished large-size ultra-thin ceramic-based solid electrolyte diaphragm is obtained.

[0015] In the process of low-temperature debinding or high-temperature sintering, the heat treatment in step S5 of the present invention applies a certain pre-tension to the electrolyte green body throughout the process, that is, a tension that hinders the bending deformation of the ceramic-based solid electrolyte membrane. The implementation method of the pre-tension can be full contact friction, local contact friction, direct tension, or any combination of the three, and the expression form of the tension includes but is not limited to these methods. By applying a certain tension, the effective sintering area of ​​the electrolyte green body is kept in a uniform heating temperature field, especially direct tension or local contact friction, and the two ends of the electrolyte green body are tightened with a tension shaft or a pressing block, and the electrolyte green body is "racked" in the furnace for sintering to form an open air heat transfer medium. During the debinding or high-temperature sintering process, accompanied by grain boundary fusion and grain growth, the gap is greatly reduced, and the green body shrinks violently. The friction between the pressing block and the electrolyte membrane is the pre-tension, which hinders the bending deformation of the ceramic-based solid electrolyte membrane and is the key to ensuring the flatness of the ceramic membrane.

[0016] Pre-tension is a resistance parallel to the plane of the ceramic diaphragm. It ensures good shrinkage performance of the membrane plane in the direction of the ceramic diaphragm plane, forms a densified ceramic diaphragm, and hinders the bending deformation of the ceramic diaphragm in the direction perpendicular to the membrane plane. The premise of pre-tension sintering is that the plane shrinkage of the ceramic diaphragm cannot be excessively sacrificed, the ceramic diaphragm cannot be damaged, and defects such as gaps, cracks, and deformations are avoided. Among them, the size of the pre-tension is a range value, which is mainly related to the strength of the green body itself, the size and shape of the green body, the combined force of grain growth and shrinkage, and the heating rate. The pre-tension should be greater than the maximum shrinkage tension of the electrolyte diaphragm that causes bending deformation, and always ensure that the ceramic-based solid electrolyte diaphragm is flat and has no bending defects. It should be less than the minimum shrinkage tension of the ceramic-based solid electrolyte diaphragm that produces crack gaps, avoiding excessive tension, shrinkage crack defects, and damage to the ceramic diaphragm. Pre-tension exists in the entire process of debinding or sintering shrinkage. The initial pre-tension can be zero, and can be kept linearly or unchanged.

[0017] Pre-tension sintering To achieve the goal of surface flatness, high densification and high mechanical strength of ceramic diaphragms, pre-tension must be applied uniformly throughout the sintering process. On the other hand, pre-tension sintering can provide a uniform heating temperature field and good debinding conditions. The effective sintering area is completely uniform air heat transfer or solid heat transfer, especially air medium heat transfer, forming an open debinding space and more uniform heat transfer conditions.

[0018] The contact surface material of the contact pre-tensioning should be non-reactive with the electrolyte green body, and for example, materials such as alumina, magnesia, and zirconia can be selected. There is no special restriction on the sintering furnace, and for example, a muffle furnace, a push plate furnace, a tube furnace, a roller furnace, or a push plate furnace and other commonly used sintering furnaces can be selected, and a rapid sintering method can also be used.

[0019] As a preferred technical solution, the chemical formula of the solid electrolyte powder is Li 1+x+y A x B 2-x Si y P 3-y O 12 (0≤x≤0.6, 0≤y≤0.6), wherein A is at least one of Al, Ga, In, and Sc, and B is at least one of Ti and Ge.

[0020] As a preferred technical solution, the dispersant is at least one of polyethylene glycol, triolein, and alkylphenol polyoxyethylene ether; as a preferred technical solution, the binder is at least one of polyvinyl butyral, polymethyl methacrylate, and polyvinyl pyrrolidone; the plasticizer is at least one of dibutyl phthalate, dioctyl phthalate, diisobutyl phthalate, and dioctyl adipate.

[0021] As a preferred technical solution, the D50 particle size of the solid electrolyte powder is 0.1 to 5 μm.

[0022] As a preferred technical solution, the solid content of the casting slurry is 30% to 70%.

[0023] As a preferred technical solution, the ceramic-based solid electrolyte diaphragm has a size of an ultra-thin medium or large square piece with a length and width of more than 10 cm×10 cm and a thickness of less than or equal to 100 μm, or an ultra-thin medium or large round piece with a diameter greater than or equal to 10 cm and a thickness of less than or equal to 100 μm.

[0024] As a preferred technical solution, in step S5, the specific steps of the one-step high-temperature heat treatment are: directly applying pre-tension to the green body obtained in step S4, and then gradually increasing the temperature to perform medium-low temperature debinding operation and high-temperature sintering operation to obtain a large-sized ultra-thin ceramic-based solid electrolyte diaphragm. As a preferred technical solution, when the pre-tension is implemented by full contact friction or partial contact friction, the unit area mass of the pressing block used to apply the pre-tension is 0.2 to 1 g / cm 2 .

[0025] As a preferred technical solution, in step S5, the specific steps of the two-step high-temperature heat treatment are: first, the green body obtained in step S4 is subjected to a medium-low temperature debinding operation after applying pre-tension, to remove organic matter in the green body, and a debinding sheet is obtained after cooling; then, the debinding sheet is re-applied with pre-tension, and the temperature is raised for high-temperature sintering to obtain a large-sized ultra-thin ceramic-based solid electrolyte diaphragm. As a preferred technical solution, when the pre-tension is implemented by full contact friction or partial contact friction, the unit area mass of the pressing block used to apply pre-tension during the medium-low temperature debinding operation is 0.2 to 1 g / cm 2 ; The unit area mass of the pressing block used to apply pre-tension during high temperature sintering operation is 0.5 to 5 g / cm 2 .

[0026] As a preferred technical solution, the debinding temperature of the medium and low temperature debinding operation is 120-800°C, the holding time is 0-10h, the heating rate is 0.1-200°C / min, and the sintering temperature of the high temperature sintering operation is 800-1050°C, the holding time is 0.5-20h.

[0027] Another aspect of the present invention is to provide a large-sized ultra-thin ceramic-based solid electrolyte membrane, which is prepared by the preparation method of the large-sized ultra-thin ceramic-based solid electrolyte membrane as described above.

[0028] The diaphragm of the present invention adopts the tape casting method to prepare the green blank, and in the sintering process, the pre-tension is applied throughout the process, which provides a uniform heating temperature field and an open debinding space for the effective sintering area of ​​the large-sized ultra-thin green blank, improves the debinding and sintering efficiency, effectively suppresses the bending deformation of the ceramic-based solid electrolyte diaphragm, and ensures the uniformity and flatness of the ceramic diaphragm, thereby realizing the batch preparation of large-sized ultra-thin solid ceramic-based solid electrolyte diaphragms with high room temperature ion conductivity, high mechanical strength, high density, and good flatness. The prepared diaphragm size can reach 10cm×10cm or more, and the thickness is controlled at 40±10μm. Ultra-thin medium and large square or round pieces. The design of the open space is conducive to the rapid volatilization of gas, improves the heat transfer performance, is suitable for rapid debinding and sintering, and thus improves production efficiency. By applying a certain tension to the ceramic diaphragm, the flatness of the diaphragm is guaranteed, the generation of defects is reduced, and the yield rate is improved. These characteristics of the diaphragm enable it to have good mechanical properties and waterproof and air-proof properties, and can maintain stable performance under different environmental conditions, providing new possibilities for the development of all-solid-state lithium batteries.

[0029] In the preferred technical solution, the ceramic-based solid electrolyte diaphragm prepared by the present invention achieves a high room temperature ionic conductivity of more than 1.0 mS / cm, significantly improving the transfer efficiency of lithium ions, thereby enhancing the overall performance of the battery. In addition, the diaphragm has an anti-flexural strength of more than 90 Mpa and a relative density of more than 98%, showing excellent mechanical strength and density, which can effectively withstand the mechanical stress of the battery during use and effectively prevent lithium dendrites from penetrating, thereby improving the safety of the battery.

[0030] Beneficial effects of the present invention:

[0031] The preparation method of the large-sized ultra-thin ceramic-based solid electrolyte diaphragm of the present invention is to prepare the large-sized green blank prepared by the casting method, and after lamination and hot pressing, innovatively apply pre-tension during the sintering process, which not only achieves the uniform flatness and high-densification structure of the ultra-thin diaphragm, but also significantly improves the mechanical strength and ionic conductivity of the diaphragm. This preparation method enables the diaphragm to have excellent electrochemical and mechanical properties while maintaining the large-sized ultra-thin characteristics, solving the problem that the performance and size of the diaphragm are difficult to achieve in the prior art. In addition, the method of the present invention also improves production efficiency and reduces costs, making it possible to mass-produce large-sized ultra-thin ceramic-based solid electrolyte diaphragms, and provides an important material basis for the development of all-solid-state lithium battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a structural schematic diagram of the green pre-tensioning method of Example 1 of the present invention.

[0033] Figure 2 It is a structural schematic diagram of the method for applying pre-tension of the green body in Example 2 of the present invention.

[0034] Figure 3 It is a structural schematic diagram of the method for applying pre-tension of the green body in Example 3 of the present invention.

[0035] Figure 4 It is a structural schematic diagram of the green pre-tensioning method of Example 4 of the present invention.

[0036] Figure 5 1 is the X-ray diffraction diagram of Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0037] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0038] Example 1

[0039] The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte diaphragm in this embodiment comprises the following steps:

[0040] S1 slurry preparation: weigh 200g of chemical formula Li 1.7 Al 0.3 Ti 1.7 Si 0.4 P 2.6 O 12 , D50 is 0.306μm solid electrolyte powder, add 16g polyvinyl butyral, 12g polyethylene glycol, 7g dibutyl phthalate and 216g xylene, ball milling and mixing for 4h to form a uniform casting slurry;

[0041] S2 tape casting and drying: the tape casting slurry obtained in step S1 is tape cast and dried to obtain a single-layer electrolyte green blank; by adjusting the height of the blade, tape casting is performed to obtain single-layer electrolyte green blanks of different thicknesses, including 15 μm, 20 μm and 25 μm;

[0042] S3 lamination hot pressing: taking one layer of single-layer electrolyte green body with thickness of 15 μm, 20 μm and 25 μm, respectively, and laminating and hot pressing to obtain electrolyte ceramic green body with thickness of about 50 μm;

[0043] S4: Cutting once: Cut the green body obtained in step S3 once using a computer plotter to obtain a square green body with a side length of 120 mm;

[0044] S5 Heat treatment: Place the square green body obtained in step S4 flat on a porous support plate and place a 2 The porous support plate is used as a cover plate and placed flat in the muffle furnace. Figure 1 The porous support plate shown in the figure is pre-tensioned, and the debinding is first carried out by medium and low temperature heat treatment. The specific debinding system is 120℃ for 1h, 300℃ for 1h, and 600℃ for 1h, and the heating rate is 5℃ / min. The temperature is cooled to room temperature with the furnace to obtain a ceramic-based solid electrolyte diaphragm debinding sheet; then the debinding sheet is placed flat on a magnesium oxide flat plate, and the unit area mass is 2g / cm 2 The magnesium oxide flat plate is used as the cover plate; according to the batch preparation requirements, the debonding sheets can be stacked in multiple layers and then the magnesium oxide flat plate is placed; the magnesium oxide flat plate is placed in a sintering furnace, and the pre-tension sintering system is 1000℃ for 6h, the heating rate is 5℃ / min, and the temperature is cooled to room temperature along with the furnace to obtain a ceramic-based solid electrolyte diaphragm sheet.

[0045] S6 secondary cutting: according to the required shape and size, the effective sintering area of ​​the ceramic-based solid electrolyte diaphragm sheet obtained in step S5 is secondary cut using a laser cutting machine to finally obtain a large-size ultra-thin ceramic-based solid electrolyte diaphragm square sheet with a length and width of 10 cm×10 cm and a thickness of 42 μm.

[0046] In the process of debinding and high-temperature sintering in this embodiment, the pre-tension is manifested as full-contact friction force, the heat transfer form is solid contact heat transfer, and the heat transfer is uniform.

[0047] The ceramic-based solid electrolyte membrane prepared by high-temperature heat treatment in the present embodiment has a smooth surface, good light transmittance, heat transfer from the support plate, uniform shrinkage, and no defects such as cracks, bends, and faults. After testing, the relative density of the ceramic-based solid electrolyte membrane reaches 96.5%, the room temperature ionic conductivity reaches 0.626mS / cm, and the flexural strength is 83Mpa.

[0048] Example 2

[0049] The raw material composition and preparation steps of the preparation method of the large-size ultra-thin ceramic-based solid electrolyte diaphragm of this embodiment are basically the same as those of Example 1, except that in the preparation method of this embodiment, the green body obtained in step S3 is cut once using a computer plotter to obtain a circular green body with a diameter of 120 mm; the electrolyte green body cut once is directly placed in a Figure 2 The circular support plate shown in the figure is covered with a cover plate of the same specification, and the unit area mass of the cover plate is 0.6g / cm 2 ; Place the circular ring support plate on four alumina ceramic columns to ensure uniform air heat transfer from top to bottom. At the same time, in step S5, a one-step high-temperature heat treatment is used for debinding and sintering, that is, the green body obtained in step S4 is directly subjected to pre-tension by placing the circular ring support plate as mentioned above, and then the temperature is gradually increased to perform medium and low temperature debinding and high temperature sintering operations. The pre-tension sintering system is 120℃ for 1h, 300℃ for 1h, 600℃ for 1h, 1000℃ for 6h, and the heating rate is 5℃ / min. The finished product is cooled to room temperature with the furnace to obtain a large-sized ultra-thin ceramic-based solid electrolyte diaphragm disc with a diameter of 10cm and a thickness of 45μm. In the high-temperature sintering process of this embodiment, the pre-tension is manifested as a local contact friction force, the effective sintering area of ​​the ceramic-based solid electrolyte diaphragm is the middle air heat transfer area, the heat transfer form is air heat transfer, and the upper and lower temperature fields are uniform.

[0050] The ceramic-based solid electrolyte membrane prepared by high-temperature heat treatment in this embodiment has a smooth surface, good light transmittance, air heat transfer, uniform shrinkage, high sintering efficiency, and no defects such as cracks, bends, and faults. After testing, the relative density of the ceramic-based solid electrolyte membrane reached 98.2%, the room temperature ionic conductivity reached 1.10mS / cm, and the flexural strength was 105Mpa.

[0051] Example 3

[0052] The raw material composition and preparation steps of the preparation method of the large-sized ultra-thin ceramic-based solid electrolyte diaphragm in this embodiment are basically the same as those in Example 1, except that, in the preparation method of this embodiment, Figure 3 As shown in the figure, the two ends of the electrolyte green body are placed flat on the alumina ceramic base respectively; then the unit area mass of 0.8g / cm 2 The alumina ceramic blocks are pressed on both ends of the green body to ensure the surface is flat; finally, the electrolyte green body is placed in a muffle furnace; in step S5, a one-step high-temperature heat treatment is used for debinding and sintering, that is, the green body obtained in step S4 is directly subjected to pre-tension through the above-mentioned placement method, and then the temperature is gradually increased to perform medium and low temperature debinding and high temperature sintering operations. The pre-tension sintering system is 120℃ for 1h, 300℃ for 1h, 600℃ for 1h, 1000℃ for 6h, and the heating rate is 5℃ / min. The finished product is cooled to room temperature with the furnace to obtain a large-size ultra-thin ceramic-based solid electrolyte diaphragm square sheet with a length and width of 10cm×10cm and a thickness of 45μm. In the high-temperature sintering process of this embodiment, the pre-tension is manifested as local contact friction.

[0053] The ceramic-based solid electrolyte membrane prepared by high-temperature heat treatment in this embodiment has a smooth surface, good air heat transfer, good exhaust performance, uniform shrinkage, high sintering efficiency, and no defects such as cracks, bends, and faults. After testing, the relative density of the ceramic-based solid electrolyte membrane reached 99.3%, the room temperature ionic conductivity reached 1.04mS / cm, and the flexural strength was 102MPa.

[0054] Example 4

[0055] The raw material composition and preparation steps of the preparation method of the large-sized ultra-thin ceramic-based solid electrolyte diaphragm in this embodiment are basically the same as those in Example 1, except that, in the preparation method of this embodiment, Figure 4As shown, the two ends of the electrolyte green body are respectively evenly wound on two tension shafts; the tension shaft is set to a tension value of 1.0N and evenly applied to the electrolyte green body; when the electrolyte green body shrinks due to heat, the tension shaft unwinds automatically, always maintaining a certain tension to ensure that the ceramic diaphragm is flat and does not hinder shrinkage; the electrolyte green body is placed in the furnace, and the middle heating zone of the furnace is the effective sintering zone. In step S5, a one-step high-temperature heat treatment is used for debinding sintering, that is, the green body obtained in step S4 is directly pre-tensioned by the above-mentioned placement method, and then the temperature is gradually increased to perform medium and low temperature debinding operations and high temperature sintering operations; the pre-tension sintering system is 120℃ for 1h, 300℃ for 1h, 600℃ for 1h, 1000℃ for 6h, and the heating rate is 5℃ / min. The finished product is cooled to room temperature with the furnace to obtain a large-size ultra-thin ceramic-based solid electrolyte diaphragm square sheet with a length and width of 10cm×10cm and a thickness of 41μm. In the present embodiment, during the high-temperature sintering process, the tension shaft directly applies pre-tension, the effective sintering area of ​​the ceramic diaphragm is the middle air heat transfer area, the heat transfer form is air heat transfer, and the heating temperature field is uniform.

[0056] The ceramic-based solid electrolyte membrane prepared by high-temperature heat treatment in this embodiment has a smooth surface, good air heat transfer, good exhaust performance, uniform shrinkage, high sintering efficiency, and no defects such as cracks, bends, and faults. After testing, the relative density of the ceramic-based solid electrolyte membrane is 98.8%, the room temperature ionic conductivity reaches 1.01mS / cm, and the flexural strength is 97Mpa.

[0057] Comparative Example 1

[0058] The preparation method of the large-sized ultra-thin ceramic-based solid electrolyte diaphragm in this comparative example has the same raw material composition and preparation steps as those in Example 1, except that, in the preparation method of this comparative example, the sintering method of the electrolyte green body is different from that in Example 1, specifically as follows: the electrolyte green body is directly placed flat on the alumina supporting plate for free sintering and shrinkage, and the sintering system is 120°C for 1h, 300°C for 1h, 600°C for 1h, 1000°C for 6h, and the heating rate is 5°C / min.

[0059] The results show that the ceramic diaphragm has an uneven surface, a large number of warping and deformation defects, cannot be tested, and is not suitable for subsequent processing applications.

[0060] Comparative Example 2

[0061] The preparation method of the large-size ultra-thin ceramic-based solid electrolyte diaphragm in this comparative example has the same raw material composition and preparation steps as those in Example 1, except that, in the preparation method of this comparative example, the sintering method of the electrolyte green body is different from that in Example 1, which is as follows: the electrolyte green body is directly placed flat on a dense alumina supporting plate, and a dense cover plate is pressed on the electrolyte green body. The sintering system is 120°C for 1 hour, 300°C for 1 hour, 600°C for 1 hour, 1000°C for 6 hours, and the heating rate is 5°C / min.

[0062] The results show that the surface of the ceramic diaphragm is smooth, but the debinding efficiency is slow and the sintering rate is slow. Due to the slow gas discharge during the debinding process, there is a small amount of uneven composition and color in some parts, and the transparency is poor. The thickness of the ceramic-based solid electrolyte diaphragm is 48μm, the relative density is 94.5%, the strength of the ceramic diaphragm is poor, the strength is 38Mpa, and the room temperature ionic conductivity is 0.429mS / cm.

[0063] The ceramic-based solid electrolyte membranes prepared in Examples 1 to 4 were subjected to X-ray diffraction tests. The results are as follows: Figure 5 As shown, the solid electrolyte membranes are all target solid ceramic-based solid electrolyte membranes, and the characteristic X-ray diffraction peaks of the crystal structure are basically consistent with the diffraction peaks of the standard card.

[0064] It can be seen from Example 1 compared with Comparative Examples 1 and 2 that the flatness of the ceramic surface can be guaranteed by pre-tension sintering. However, due to the limitation of the debinding process, the ceramic-based solid electrolyte diaphragm sintered by full-contact pre-tension sintering has poor uniformity and poor performance. In order to avoid the limitation of debinding, a two-step pre-tension sintering is adopted. The pre-tension debinding treatment is first performed, and then the pre-tension high-temperature sintering is performed. The room temperature ionic conductivity is greatly improved, the flexural strength is greatly improved, the composition is uniform, the appearance is good, and the transparency is high. The effective sintering area is solid heat transfer, and two-step sintering is required, and the efficiency is relatively low. In Examples 2-4, through pre-tension sintering, the effective sintering area is all air heat transfer, forming a uniform heating temperature field and an open debinding space, avoiding the obstruction of other objects, improving the debinding efficiency and sintering performance, and realizing one-step sintering. Compared with Example 1, various performance indicators are significantly improved, and the production efficiency is high. The pre-tension sintering method of the present invention has the characteristics of simple process and convenient operation, and can realize low-cost and large-scale preparation of ultra-thin solid ceramic-based solid electrolyte diaphragms.

[0065] Embodiment 5-10

[0066] The preparation method of the large-sized ultra-thin ceramic-based solid electrolyte membrane of Example 5-10 has the same raw material composition and preparation steps as Example 2. The solid electrolyte powder of Example 5 has a chemical formula of Li 1.5 Al 0.3Ti 1.7 Si 0.2 P 2.8 O 12 ; The components of the solid electrolyte powder used in Example 6 have a chemical formula of Li 1.6 Al 0.3 Ti 1.7 Si 0.3 P 2.7 O 12 ; The components of the solid electrolyte powder used in Example 7 have a chemical formula of Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 ; The components of the solid electrolyte powder used in Example 8 have a chemical formula of Li 1.4 Al 0.4 Ti 1.6 P 3 O 12 ; The components of the solid electrolyte powder used in Example 9 have a chemical formula of Li 1.45 Al 0.45 Ge 0.2 Ti 1.35 P 3 O 12 ; The components of the solid electrolyte powder used in Example 10 have a chemical formula of Li 1.3 Al 0.3 Sn 0.35 Ti 1.35 P 3 O 12 The ceramic-based solid electrolyte membranes prepared in Examples 5-10 were subjected to various performance tests under the same test conditions. The results are shown in Table 1. Table 1

[0067] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane, characterized in that: The preparation method comprises the following steps: S1 slurry preparation: take a certain mass of solid electrolyte powder, add a certain proportion of dispersant, binder, plasticizer and solvent, and form a uniform casting slurry after ball milling and dispersion; S2 tape casting and drying: the tape casting slurry obtained in step S1 is tape cast and dried to obtain a single-layer electrolyte blank; S3 lamination hot pressing: lamination hot pressing the single-layer electrolyte green body obtained in step S2 according to the required thickness to obtain a green body of a certain thickness; S4: cutting the green body obtained in step S3 into the required shape and size; S5 heat treatment: the green body of a certain shape and size obtained in step S4 is subjected to a one-step high-temperature heat treatment or a two-step high-temperature heat treatment by applying pre-tension to obtain a ceramic-based solid electrolyte diaphragm sheet; S6 secondary cutting: according to the required shape and size, a laser cutting machine is used to perform secondary cutting on the effective sintering area of ​​the ceramic-based solid electrolyte diaphragm sheet obtained in step S5, and finally a finished large-size ultra-thin ceramic-based solid electrolyte diaphragm is obtained.

2. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: The chemical formula of the solid electrolyte powder is Li 1+x+y A x B 2-x Si y P 3-y O 12 (0≤x≤0.6, 0≤y≤0.6), wherein A is at least one of Al, Ga, In, and Sc, and B is at least one of Ti and Ge.

3. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: The dispersant is at least one of polyethylene glycol, triolein, and alkylphenol polyoxyethylene ether; the binder is at least one of polyvinyl butyral, polymethyl methacrylate, and polyvinyl pyrrolidone; and the plasticizer is at least one of dibutyl phthalate, dioctyl phthalate, diisobutyl phthalate, and dioctyl adipate.

4. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: The D50 particle size of the solid electrolyte powder is 0.1 to 5 μm.

5. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: The solid content of the casting slurry is 30% to 70%.

6. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: The ceramic-based solid electrolyte diaphragm has a size of an ultra-thin medium-to-large square piece with a length and width of more than 10 cm×10 cm and a thickness of less than or equal to 100 μm, or an ultra-thin medium-to-large round piece with a diameter of greater than or equal to 10 cm and a thickness of less than or equal to 100 μm.

7. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: In step S5, the specific steps of the one-step high-temperature heat treatment are: directly applying pre-tension to the green body obtained in step S4, and then gradually increasing the temperature to perform medium-low temperature debinding operation and high-temperature sintering operation to obtain a large-sized ultra-thin ceramic-based solid electrolyte membrane.

8. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 1, characterized in that: In step S5, the specific steps of the two-step high-temperature heat treatment are: first, the green body obtained in step S4 is subjected to medium-low temperature debinding operation after applying pre-tension to remove organic matter in the green body, and a debinding sheet is obtained after cooling; then, pre-tension is re-applied to the debinding sheet, and the temperature is increased for high-temperature sintering to obtain a large-sized ultra-thin ceramic-based solid electrolyte membrane.

9. The method for preparing a large-sized ultra-thin ceramic-based solid electrolyte membrane according to claim 7 or 8, characterized in that: The debinding temperature of the medium-low temperature debinding operation is 120-800°C, the holding time is 0-10h, and the heating rate is 0.1-200°C / min. The sintering temperature of the high temperature sintering operation is 800-1050°C, and the holding time is 0.5-20h.

10. A large-sized ultra-thin ceramic-based solid electrolyte diaphragm, characterized in that: The ceramic-based solid electrolyte membrane is prepared by the method for preparing a large-size ultra-thin ceramic-based solid electrolyte membrane as claimed in any one of claims 1 to 9.